Outcome of Solifenacin Monotherapy and Combined Solifenacin and Mirabegron Therapy in Patient with Overactive Bladder - Majumder, Sharif Muhammad Mahmudul Hasan; Farhana, Fatima; Asaduzzaman , Muhammad; Amin, Mohammad Ruhul; Hasan , Mohammad Masum; Begum, Taslima (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Overactive bladder has a profound detrimental effect on quality of life. In the vast majority of the patients, the management plan entails behavioral modification and the anti-muscarinic drug solifenacin, which has considerable side effects and lower patients satisfaction rate. Mirabegron, a β3-adrenoceptor agonist, significantly improves OAB symptoms and plays an important role in the management algorithm. Objectives: This study examined the effectiveness and safety of solifenacin monotherapy versus mirabegron and solifenacin combination therapy in the treatment of OAB. Methods: This study was conducted as a quasi-experimental model. A total of 90 patients were included in the study through purposive sampling and divided into two comparison groups: Group A (control group) receiving Solifenacin (5 mg) once daily at night for 12 weeks, and Group B (experimental group) receiving a combination of Solifenacin (5 mg) and Mirabegron (25 mg) nightly for the same period. Follow-up visits were conducted at 4, 8, and 12 weeks to track the number of micturitions, urgency, urge incontinence, nocturia, and voided volume over 24 hours. Data analysis was conducted using SPSS version 22, and the chi-square test was used to compare percentages of different outcome variables. A p-value of less than 0.05 was considered statistically significant. Results: Solifenacin (5 mg) monotherapy and combined miragraben (25 mg) and solifenacin (5 mg) showed comparable efficacy in alleviating symptoms of OAB, but greater improvement with regard to frequency of micturition, urgency, and urge incontinence were showed in the combined therapy group. Conclusion: The combination of Solifenacin and Mirabegron provides a more effective treatment for overactive bladder compared to Solifenacin alone. Although the combined treatment group experienced more adverse effects, these differences were not statistically significant between the two groups. Since the adverse effects were generally mild and temporary, the combined therapy remains a viable option for managing overactive bladder. J Com Med Col Teachers Asso July 2024; 28(2): 75-81